Pengaruh Kemudahan dan Kepercayaan Terhadap Niat Pembelian Secara Online pada Platform E-Commerce Lazada Indonesia - Inggri Septianie; Mariati Tirta Wiyata (Institut Manajemen Wiyata Indonesia, 2020)
This study aims to examine the effect of ease of use and customer trust on online purchase intentions on the Lazada Indonesia e-commerce platform. The research method used is quantitative. Data collection techniques through surveys. The research location is in Sukabumi City, West Java. Research respondents consisted of 100 visitors to the Lazada Indonesia e-commerce platform. Information was collected from respondents using a questionnaire. Testing the quality of the instrument (questionnaire) using the validity test and reliability test. Hypothesis testing used multiple linear regression analysis, consisting of t test and F test. The results showed that partially and simultaneously the ease of use and customer trust variables had a positive and significant effect on the purchase intention variable. Respondents stated that Lazada Indonesia's e-commerce platform is easy to use. Respondents also stated that Lazada Indonesia is able to provide the products needed and Lazada Indonesia will always protect its reputation (integrity).